2021
DOI: 10.1111/idh.12511
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of orthodontic toothbrush versus conventional toothbrush on plaque and gingival index reduction: A systematic review and meta‐analysis

Abstract: Objective: In orthodontic patients submitted to oral hygiene instruction, what is the efficacy of orthodontic toothbrush (O-TB) versus conventional toothbrush (C-TB) on plaque and gingival index reduction in randomized and non-randomized controlled clinical trials? Methods: Electronic database search was performed on PubMed, ClinicalTrials.gov, Cochrane Library and Google Scholar. Database research, study selection, data extraction and ROBINS-I and Risk of Bias Tool 2.0 analysis were conducted by two independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Plaque on teeth is characterized as a soft, lingering substance that is present on the tooth's surface and is challenging to eliminate with a simple water rinse [19,20]. Dental plaque is the main cause of inflamed gums (gingivitis), which are characterized by erythema of the marginal gingiva where it meets the teeth as well as mild edema and hemorrhage from the gingival border [21][22][23]. Personalized dental hygiene is the preservation of mouth hygiene for the sustenance of proper oral health.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque on teeth is characterized as a soft, lingering substance that is present on the tooth's surface and is challenging to eliminate with a simple water rinse [19,20]. Dental plaque is the main cause of inflamed gums (gingivitis), which are characterized by erythema of the marginal gingiva where it meets the teeth as well as mild edema and hemorrhage from the gingival border [21][22][23]. Personalized dental hygiene is the preservation of mouth hygiene for the sustenance of proper oral health.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent meta-analysis, gingival bleeding is not modified by the O-TB, but major plaque removal of the O-TB by 1.72 (95% confidence interval [CI] = 0.83-2.61; p = 0.0001) was validated [ 22 ]. However, additional randomized clinical trials are warranted to clarify the real clinical orthodontic relevance of the orthodontic toothbrush due to the considerable heterogeneity and quality of the data [ 22 ]. Our study found no significant difference between the C-TB and O-TB.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the v-shaped bristles encourage better oral hygiene by increasing the contact between toothbrush bristles and orthodontic apparatus [ 15 ]. The O-TB is more effective in removing plaque than the C-TB, according to a recent systematic review and meta-analysis on the topic, but this improvement is not fully understood, underscoring the need for additional randomized clinical trials to evaluate the effects of using an O-TB in comparison to a C-TB [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 It is known that the most frequently used fixed appliances, influence plaque and food retention affecting oral hygiene level, and many authors investigated various hygiene products prophylaxis in these patients. For example, Sivaramakrishnan 12 compared the effectiveness of electric toothbrush and manual toothbrush in patients undergoing treatment with fixed appliances and proved the use of the first one, while Felipe Franco Marçal et al 13 showed the usefulness of using special orthodontic toothbrush in the same category of patients.…”
Section: Introductionmentioning
confidence: 99%